Stress analysis in composite laminates - Chew, Hui Da (2018)
A numerical stress analysis using the Boundary Element Method (BEM) was used to analyze the stress intensity factor of the orthotropic unidirectional lamina with a center circular hole under steady tensile loading. AS4/3502 Graphite-Epoxy was used in this experiment. Results of the location, magnitude of normalized stress intensity factor due to the variation off-axis angle and angle where crack start to initiate are presented. It was deduced that locations, where the crack starts to propagate in the composites, may not necessarily occur at the locations that experience the highest stress concentrations which are at 0 or 180 degrees